2015
DOI: 10.1063/1.4914467
|View full text |Cite
|
Sign up to set email alerts
|

Reaction enhancement of initially distant scalars by Lagrangian coherent structures

Abstract: Turbulent fluid flows have long been recognized as a superior means of diluting initial concentrations of scalars due to rapid stirring. Conversely, experiments have shown that the structures responsible for this rapid dilution can also aggregate initially distant reactive scalars and thereby greatly enhance reaction rates. Indeed, chaotic flows not only enhance dilution by shearing and stretching but also organize initially distant scalars along transiently attracting regions in the flow. To show the robustne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…A similar correspondence between regions of intense mixing and attracting Lagrangian structures has been observed in previous studies. 5,41 It is clear that mixing is significantly enhanced in the second response branch (where the SA and A-IV modes occur) compared to the case of the near-stationary cylinder, but is not significantly affected by the S-I mode. Symmetric shedding generally occurs when the excitation or , at U r St/ f * = 0.58 while the SA mode was dominant.…”
Section: Mixing In the Wakementioning
confidence: 92%
See 2 more Smart Citations
“…A similar correspondence between regions of intense mixing and attracting Lagrangian structures has been observed in previous studies. 5,41 It is clear that mixing is significantly enhanced in the second response branch (where the SA and A-IV modes occur) compared to the case of the near-stationary cylinder, but is not significantly affected by the S-I mode. Symmetric shedding generally occurs when the excitation or , at U r St/ f * = 0.58 while the SA mode was dominant.…”
Section: Mixing In the Wakementioning
confidence: 92%
“…This case was chosen as it exhibited the strongest cross-wake mixing Regions of high |∇C| correspond to points at which you would expect to find the strongest mixing if the streams were "active," e.g., streams of reactive chemical agents 5 or in various biological processes such as the fertilisation of marine species. 41 The fields contains regions where |∇C|D > 8.5, which correspond to points at which the two fluid streams came very close together, i.e., the separation between the two streams is less than the resolution of the PIV fields.…”
Section: Mixing In the Wakementioning
confidence: 99%
See 1 more Smart Citation
“…If the initial separation distance between the two scalars is smaller than the largest coherent length scales of the local flow, the two scalar fields develop similar instantaneous spatial distributions. While it is easier to envision these processes in simple flows, recent numerical simulations (Pratt et al 2015) have shown that in more complex 2D flows involving multiple interacting vortices, initially distant scalars coalesce in regions of intense mixing and attracting Lagrangian coherent structures.In aquatic ecosystems, structured flows can facilitate stirring and diffusion to enhance reactions or population growth by bringing together species and nutrients (e.g., Richards and Brentnall 2006). Structured flows stir any introduced scalars into thin filament shells (Garrett 1983), enhancing local scalar gradients, increasing the interfacial area of the scalar through chaotic stretching and folding (Hinch 1999), leading finally to increased mixing by molecular diffusion.…”
mentioning
confidence: 99%
“…We specify an unsteady velocity field v that has seen extensive use as a testbed for LCS analysis [142,143,109,144,1,145,38,146,102,77,147,78,79,148,76,88]: the double gyre flow as introduced by Shadden et al [75]. The velocity v = (v 1 , v 2 ) takes the form where the function h is defined by…”
Section: Passive Scalar Advectionmentioning
confidence: 99%